Sutureless Technique for Primary Total Anomalous Pulmonary Venous Connection Repair: An Updated Meta-Analysis - Zhao, Lu; Pan, Zhengxia; Wu, Chun; Shen, Lianju; Wu, Yuhao (Frontiers in Cardiovascular Medicine, 2022)
Background An updated meta-analysis was performed to explore the clinical outcomes following the sutureless repair in patients with total anomalous pulmonary venous connection (TAPVC) and compare outcomes between the sutureless technique and conventional surgery. Methods A systematic search of PubMed, Ovid-Embase, and Cochrane Library (CENTRAL) for relevant published studies that reported the clinical outcomes of the sutureless technique in children with TAPVC was performed in February 2022. The publication language was restricted to English. Results Eleven studies meeting the inclusion criteria were included, involving 771 patients in total. Following the sutureless technique, the incidences of postoperative pulmonary venous obstruction (PVO) and reoperations due to PVO were 3.3% (95% confidence interval (CI), 1.3% to 5.3%) and 1.8% (95% CI, 0.3% to 3.3%), respectively. The early and late mortality rates were 3.2% (95% CI, 1.0% to 5.3%) and 2.5% (95% CI, 0.7% to 4.3%), respectively. Compared with conventional surgery, the sutureless technique significantly reduced the incidences of postoperative PVO (odds ratio (OR), 0.16; 95% CI, 0.08 to 0.33; P<0.00001), reoperations due to PVO (OR, 0.25; 95% CI, 0.10 to 0.63; P=0.003) and early mortality (OR, 0.40; 95% CI, 0.21 to 0.79; P=0.008). However, no significant difference was found between conventional surgery and the sutureless technique concerning late mortality (OR, 0.63; 95% CI, 0.13 to 3.00; P=0.58). Conclusions The sutureless technique is beneficial for the primary repair of TAPVC regarding postoperative PVO, reoperations due to PVO, and early mortality. However, the level of evidence is of low quality. Prospective cohort studies or randomized control trials should be designed to evaluate the safety and effectiveness of sutureless techniques for TAPVC.